Radiofrequency catheter ablation of atrioventricular node reentrant tachycardia in children with limited fluoroscopy. (1st June 2017) - Swissa, Moshe; Birk, Einat; Dagan, Tamir; Naimer, Sody Abby; Fogelman, Michal; Einbinder, Tom; Bruckheimer, Elchanan; Fogelman, Rami
Abstract: Background: Limited fluoroscopy cryo-ablation using a 3D electro-anatomical system (3DS) has been used for AVNRT in children. We aimed to facilitate a fluoroscopy limited approach of RF ablation of AVNRT in children. Methods: A retrospective study was performed of procedure parameters in children undergoing RF ablation of AVNRT in 75 consecutive children (June 2011 to November 2013 — Group A) using standard fluoroscopy techniques compared to those of 64 consecutive children (December 2013 to May 2015 — Group B), using a fluoroscopy limited approach with 3DS. Results: The acute success rate was 98.7% (74/75) and 98.4% (63/64) for groups A and B, respectively. The recurrence rate was 2.7% (2/74) and 0% (0/63) with a mean follow-up period of 45.5 ± 12.1 and 14.3 ± 6.1 months for group A and group B, respectively. The mean procedure and fluoroscopy times were significantly lower for group B compared to group A (119 ± 37 (43–203) and 0.83 ± 1.04 (0.05–3.83) minutes versus 146 ± 53 (72–250) and 16.1 ± 8.9 (4.39–55) minutes, p  < 0.003 and p  < 0.0001, respectively). There were no ablation-related complications. Conclusions: A fluoroscopy limited approach for RF ablation of AVNRT in children using a 3DS is easily acquired and adapted, and significantly reduces the fluoroscopy and procedure time with excellent efficacy, safety and low recurrence rate. Condensed ABSTRACT: This study confirmed that a 3D mapping system (3DS) to guide ablations of AVNRT in children reduces radiation exposure. Combined, limited fluoroscopy and 3DS in a methodology that resembles the familiar conventional fluoroscopy approach for RF ablation of AVNRT in children is proposed. Combined limited fluoroscopy and RF-energy in children with AVNRT are associated with a shorter procedure time, minimal fluoroscopy time, a high success rate and a low recurrence rate.